2010
DOI: 10.1038/jhg.2010.82
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study to identify genetic variants present in Japanese patients harboring intracranial aneurysms

Abstract: An intracranial aneurysm (IA), which results in a subarachnoid hemorrhage with a high mortality on rupture, is a major public health concern. To identify genetic susceptibility loci for IA, we carried out a multistage association study using genome-wide single nucleotide polymorphisms (SNPs) in Japanese case-control subjects. In this study, we assessed evidence for association in standard approaches, and additional tests with adjusting sex effects that act between genetic effect and disease. Consequently, five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 25 publications
(26 reference statements)
0
31
1
Order By: Relevance
“…14 One associated SNP located on chromosome 7 (rs4628172 G.T) is within the TMEM195 gene, which encodes transmembrane proteins, possibly involved in fatty acid biosynthesis and iron binding. 11,13 Further associated SNPs from the latest GWAS include variants on chromosome 12q22 (rs6538595, rs11112585, and rs2374513) within the C12orf75 gene.…”
Section: -252)mentioning
confidence: 99%
See 1 more Smart Citation
“…14 One associated SNP located on chromosome 7 (rs4628172 G.T) is within the TMEM195 gene, which encodes transmembrane proteins, possibly involved in fatty acid biosynthesis and iron binding. 11,13 Further associated SNPs from the latest GWAS include variants on chromosome 12q22 (rs6538595, rs11112585, and rs2374513) within the C12orf75 gene.…”
Section: -252)mentioning
confidence: 99%
“…More recently, genome-wide association studies (GWAS) have identified novel genetic loci strongly associated with IAs, [9][10][11][12][13][14] but these still explain only a fraction of the genetic risk.…”
mentioning
confidence: 99%
“…However, if ethnicity-specific risk factors exist, these loci may impose a bias from population stratification and this may appear as 'noise' in a large study. Although the current study reported by Akiyama et al 5 is ambitious and challenging, it may have various drawbacks. Particularly, the hypothesis of actin remodeling in the ELN/LIMK pathway is, as yet, unsubstantiated and requires a more substantial biological explanation.…”
mentioning
confidence: 83%
“…In 2010, three new loci (18q11.2, 13q13.1 and 10q24.32) were found and two previously identified loci (8q11.23 and 9p21.3) were confirmed by an international consortium that included a team from Japan. 4 In this issue of the journal, the Japanese team, Akiyama et al, 5 report five SNPs (rs1930095 of intergenic region (9q31), rs4628172 and rs7781293 of TMEM195 (7p21), rs7550260 of ARHGEF11 (1q23) and rs9864101 of IQSEC1 (3p25)) in a Japanese population. They speculate that, because the three genes may have a role in actin remodeling in the ELN/LIMK pathway, these genes may be IA susceptibility ones.…”
mentioning
confidence: 99%
See 1 more Smart Citation